Legal Policies for the Protection of Children's Rights After Divorce: A Comparative Study of Malaysia, Singapore, and Indonesia - Qadriah, Fauza; Yuslem, Nawir; Yadi Harahap, Mhd. (Universitas Dharma Wacana, 2025)
Divorce has a significant impact on children, particularly concerning the fulfillment of their custody, financial support, and psychosocial well-being. This study analyzes legal policies on the protection of children's rights after divorce in indonesia, malaysia, and singapore through a comparative law approach. Using normative and empirical juridical methods, this research examines existing legal regulations and the effectiveness of their implementation based on court case data, divorce statistics, and interviewxs with legal experts. The findings indicate that while all three countries have regulations ensuring children's rights post-divorce, gaps remain in their implementation. In indonesia, weak enforcement mechanisms for child support lead to many children losing their financial entitlements. Malaysia’s dual legal system (sharia and civil) sometimes delays the execution of child support rights. Meanwhile, singapore has developed an integrated system with a therapeutic justice approach, including mandatory mediation and more effective enforcement mechanisms. This study recommends establishing a child support enforcement unit in indonesia, harmonizing legal procedures in malaysia, and enhancing psychosocial support programs in singapore. Legal reforms incorporating best practices from these three countries are expected to improve the protection of children's rights after divorce.